2012
DOI: 10.3329/icpj.v1i9.11620
|View full text |Cite
|
Sign up to set email alerts
|

Development of RP-HPLC method for the estimation of Rasagiline mesylate in bulk and tablet dosage forms

Abstract: A simple RP-HPLC method for the determination of Rasagiline Mesylate in bulk and tablet dosage form was developed. Numerous HPLC conditions were tested for determination of rasagiline. The best result was achieved by using Purosphere star RP-18, (150×4.6mm), 5µm column and a mobile phase consisting of Potassium Orthophosphate: Acetonitrile (60:40 v/v) adjusted to pH 7.0(±0.05) with Ammonia solution, a flow rate of 1.5 ml/min with ultraviolet detection at 210nm. The correlation coefficients for calibration curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…[1][2][3][4][5] Among them, the asymmetric Aldol reaction and Domino Knoevenagel Michael cyclization reaction are the most powerful and efficient approaches for accessing various enantiomerically enriched biomolecules. 6,7 The core framework '3-alkyl-3-hydroxyindolin-2-ones' is present in a large number of natural products [8][9][10][11][12][13][14] and drug molecules [15][16][17][18][19] such as maremycins, 17 arundaphine, 20 donaxaridine, 21 paratunamide, 22 , (R)-convolutamydines A, B and E, [23][24][25][26][27] ustraminol, 28 diazonamides, [29][30][31][32][33] leptosin D, 34 3 0 -hydroxyglucoisatisin, 35 CPC-1, 36 3-hydroxy welwitindolinones C, 37 TMC-95 (A-D), [38][39][40] celogentin K, 41 dioxibrassinin 42 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among them, the asymmetric Aldol reaction and Domino Knoevenagel Michael cyclization reaction are the most powerful and efficient approaches for accessing various enantiomerically enriched biomolecules. 6,7 The core framework '3-alkyl-3-hydroxyindolin-2-ones' is present in a large number of natural products [8][9][10][11][12][13][14] and drug molecules [15][16][17][18][19] such as maremycins, 17 arundaphine, 20 donaxaridine, 21 paratunamide, 22 , (R)-convolutamydines A, B and E, [23][24][25][26][27] ustraminol, 28 diazonamides, [29][30][31][32][33] leptosin D, 34 3 0 -hydroxyglucoisatisin, 35 CPC-1, 36 3-hydroxy welwitindolinones C, 37 TMC-95 (A-D), [38][39][40] celogentin K, 41 dioxibrassinin 42 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the low fluorescence intensity of isatin N ‐phenylsemicarbazone derivatives due to the predominant non‐radiative excited state deactivation, results of this study can be a useful supplement for better understanding of complex processes in solution of effective colorimetric sensors based on isatin N ‐phenylsemicarbazone. Moreover, because isatin semicarbazones are often biologically active, concept of associate/hydrazide/hydrazonol equilibrium in solution can help other researches in this field to deeply understand the structure–property and structure–biological activity relationships of some isatin semicarbazones. Structure of studied isatin N ‐phenylsemicarbazone E ‐isomers is depicted in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…It exhibits endogamous activity in mammals (Chaudhary et al, 2013) and has shown cardioinhibitory effects on a frog's heart, and hypotensive, respiratory depression and antidiuretic effects (Pandeya et al, 2005). Isatin also possess anticancer (Khan et al, 2015), antioxidant (Sammaiah & Pragathi, 2014), antiviral (Gomathi et al, 2013), antimicrobial (Saxena et al, 2015), analgesic (Pal et al,201), anti-inflammatory (Hajare & Chinchole, 2013), antitubercular (Aboul-fadl & BinJubair, 2010), anticonvulsant (Raj, 2012) and antianxiety (Grewal, 2014) activities.…”
Section: Structure Descriptionmentioning
confidence: 99%